Fracture Behavior of Layered Alumina Microstructural Composites with Highly Textured Layers. Issue 5 (5th April 2013) - Pavlacka, Robert; Bermejo, Raul; Chang, Yunfei; Green, David J.; Messing, Gary L.; Parthasarathy, T.
<x xml:space="preserve">Abstract</x> A new class of layered microstructural composites that combines equiaxed and textured alumina layers was fabricated. Template loading was used to change the texture fraction and porosity in the textured layers. Due to the thermal expansion anisotropy of the textured layers, residual compressive stresses as high as 100 MPa were achieved during cooling from the sintering step. Fracture experiments showed that the interface between the basal planes of highly oriented alumina grains in the textured layers changes from a "strong interface" to a "weaker interface" as the porosity changes from 1% to 5%. Composites with 5% porous textured layers show both crack bifurcation and crack deflection in the textured layers. Crack deflection is attributed to the anisotropic fracture energy of the oriented microstructures and crack bifurcation is ascribed to the compressive stresses that arise from the thermal expansion mismatch between adjacent layers.